The Effect of Candlenut Shell Ash and Biochar and NPK Fertilization on Corn (Zea mays L.) Growth and Production - Tesalonika Sembiring; Sarifuddin; Mukhlis (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Corn (Zea mays L.) is a strategic food crop that requires an adequate supply of essential nutrients, particularlynitrogen, phosphorus, and potassium, to support optimal growth and yield. The increasing accumulation ofcandlenut shells, which are difficult to decompose due to their high lignin content, has contributed toenvironmental pollution. Processing candlenut shells into ash or biochar can enhance their value. Both candlenutshell ash and biochar can serve as soil ameliorants, improving soil fertility by increasing soil pH, organic carbon,and cation exchange capacity (CEC), especially in ultisol soils characterized by low fertility. Ultisol soils aretypically acidic, have high aluminum saturation, and low CEC. Ash, an inorganic material rich in calcium, isproduced through complete combustion, whereas biochar is a carbon-rich material generated via pyrolysis. Thisstudy aimed to evaluate the effects of candlenut shell ash and biochar on the availability of N, P, and K nutrientsin corn (Zea mays L.) cultivated in Samosir Regency. The research was conducted in Pangururan, Samosir Regency,from June to November 2024. The results demonstrated that applying candlenut shell ash and biochar asameliorants enhanced corn growth. Candlenut shell ash was more effective than biochar at improving NPKfertilizer efficiency. Specifically, the application of candlenut shell ash at 10 tons per hectare, combined with asingle NPK fertilizer dose (treatment A12), yielded the best corn growth. Based on these findings, the use ofcandlenut shell ash is recommended for corn cultivation on ultisol soils, as it more effectively increases nutrientavailability and plant growth, thereby potentially enhancing corn productivity sustainably.